The Interplay of Self-Efficacy, Foreign Language Anxiety, Speaking Performance, and Oral Proficiency among EFL Undergraduate Students - Rizky Andre Zaelani; Nur Afidah Kusuma Diyanti; Nadiya Riska Amanda; Neneng Sri Lestari (Indonesian Journal of Science, Technology and Humanities, 2026)
This study examined the relationships among self-efficacy, foreign language anxiety, speaking performance, and oral proficiency among EFL undergraduate students. A quantitative correlational design was employed involving 284 students from the English Education Study Programs at STKIP Al Maksum Langkat and Universitas Muhammadiyah Sumatera Utara (UMSU). Participants were selected using proportionate stratified random sampling. Data were collected through the English Speaking Self-Efficacy Scale, the Foreign Language Classroom Anxiety Scale (FLCAS), and an oral speaking test. The instruments demonstrated satisfactory reliability, with Cronbach's alpha coefficients ranging from 0.89 to 0.95. Data were analyzed using descriptive statistics, Pearson correlation, multiple regression, and Structural Equation Modeling (SEM) with AMOS 28.0. The findings indicated that self-efficacy was positively associated with speaking performance (r = .684, p < .001), whereas foreign language anxiety was negatively associated with speaking performance (r = −.611, p < .001). Furthermore, self-efficacy positively predicted speaking performance (β = .51), while foreign language anxiety exerted a negative effect (β = −.37). Together, both variables explained 61.2% of the variance in speaking performance (R² = .612). The findings suggest that enhancing students' self-efficacy and reducing foreign language anxiety are essential for improving speaking performance and oral proficiency among EFL undergraduate students